Issues Related to Implementation of Scheduled Tribes and Other Traditional Forest-dwellers (Recognition of Forest Rights) Act 2006, in Bihar: Fieldwork from Gaya District, Bihar. (June 2018) - Kishore, Kunal
Forest Rights Act was passed by the Indian Parliament in 2006, and the states have implemented it since 2008. The Act recognises rights of the forest-dwelling communities on forest lands. This article tries to analyse the issues related to its implementation in Bihar through the fieldwork done in the villages of Gaya district. In case of Bihar, apart from tribals, the largest beneficiaries of this Act are the Mahadalits who qualify as Other Traditional Forest-Dwellers in this law. Bhyuians, a scheduled caste, have managed to acquire (by Kabza, possession) forest land despite the non-recognition of their entitlement rights by the state. They have been in a constant interaction with the administrative apparatus of state in holding on to their Kabza over forest land without resorting to any act of physical violence. Their basic demand is that the state government should recognise the legality of their Kabza on the land.